Preparation method of water-repellent acid-proof non-woven fabric for waste gas filtration of pickling production line

By modifying fiber blending, gradient hydroentangling reinforcement, and surface functionalization treatment, the corrosion resistance and structural stability problems of the waste gas filter material in the pickling production line were solved, and the preparation of nonwoven fabric with high efficiency filtration and long service life was achieved.

CN120989834APending Publication Date: 2025-11-21WUXI HONGQING NON WOVEN FABRIC CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511062486.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-31
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

Existing acid pickling production line exhaust gas filter materials are deficient in terms of corrosion resistance, water repellency, and structural stability, and are susceptible to corrosion by acidic gases, clogging by oily particles, and reduced air permeability.

Method used

A high-strength and breathable three-dimensional fiber network is formed by blending polyimide and polytetrafluoroethylene modified fibers, combining polyphenylene sulfide and PE/PP core fibers, and reinforcing with gradient hydroentangling and crosslinking with epoxy modified polyurethane. The surface is coated with CaF2-PVDF composite emulsion and etched with micro-pit array.

Benefits of technology

It achieves high filtration accuracy under strong acid, high temperature and high humidity environments, improves mechanical strength and extends service life, and has excellent corrosion resistance and anti-clogging ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005526028550000081
    Figure BDA0005526028550000081
  • Figure BDA0005526028550000091
    Figure BDA0005526028550000091
Patent Text Reader

Abstract

The invention discloses a preparation method of a water-repellent and acid-proof non-woven fabric for waste gas filtration of a pickling production line, and the preparation method comprises the following steps: S1, preparing modified acid-proof fibers, S2, mixing the fibers to form a net, S3, carrying out gradient spunlace reinforcement, S4, carrying out interface strengthening treatment, and S5, carrying out surface functional coating. The structural stability, corrosion resistance and surface functionalization of the pickling waste gas filtering non-woven fabric are enhanced through multi-stage composite modification, and the core is endowed with an acid-resistant barrier through polyimide / polytetrafluoroethylene blending modified fibers. A high-strength breathable three-dimensional fiber network substrate is formed by combining single-spunlace medium-pressure initial shaping in a pre-reinforcing area, double-spunlace high-pressure progressive entanglement in a flat net area and three-spunlace pressure-reduction refining surface in a round drum area; through epoxy modified polyurethane crosslinking interface strengthening, a continuous high-molecular protective layer is constructed, and permeation of an acid medium is effectively blocked; and through double-sided coating of the CaF2-PVDF composite emulsion, the slow-release corrosion prevention and hydrophobicity are enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nonwoven fabric preparation technology, specifically to a method for preparing a water-repellent and acid-resistant nonwoven fabric for filtering exhaust gas in an acid pickling production line. Background Technology

[0002] The waste gas generated in pickling production lines contains high concentrations of acidic gases, oily particles, and high-temperature water vapor, placing stringent requirements on the corrosion resistance, water repellency, and structural stability of filter materials. Traditional filter materials mostly use ordinary non-woven fabrics or composite membrane structures, but these have significant limitations. Conventional non-woven fabrics are mainly composed of polypropylene or polyester fibers, formed through needle punching or hot rolling processes. Although they possess a certain mechanical strength, the hydrophilic groups on the fiber surface easily adsorb acidic water vapor, leading to material swelling and strength reduction. At the same time, oily particles in pickling waste gas easily adhere to the fiber gaps, clogging the pores and promoting microbial growth, further reducing filtration efficiency and service life.

[0003] To improve acid resistance, existing technologies often use glass fiber or metal fiber as reinforcing materials and achieve surface water repellency through a polytetrafluoroethylene (PTFE) coating. However, this process has three major drawbacks. First, the interfacial bonding between the reinforcing fiber and the matrix fiber is insufficient, making it prone to delamination and peeling under long-term acidic conditions, leading to structural collapse. The blending of glass fiber and polyester relies on high-temperature melting, but temperature fluctuations in pickling exhaust gas can easily trigger thermal stress cracking, weakening the material's overall integrity. Second, the surface coating process struggles to achieve uniform coverage. While PTFE spraying can impart water repellency, the coating easily covers the pores between fibers, reducing air permeability; uncovered areas are exposed to acidic media, accelerating localized corrosion and perforation. Third, existing materials lack dynamic anti-clogging capabilities. Oily particles in pickling exhaust gas mix with acidic water vapor to form a viscous substance that easily adheres to and clogs the fiber network. Traditional cleaning methods struggle to thoroughly remove deep-seated contaminants, resulting in a sharp increase in filtration resistance and the need for frequent filter media replacement. Summary of the Invention

[0004] This invention provides a method for preparing a water-repellent and acid-resistant nonwoven fabric for filtering exhaust gas from an acid pickling production line.

[0005] The technical solution of this invention is: a method for preparing a water-repellent and acid-resistant nonwoven fabric for filtering exhaust gas in an acid pickling production line, comprising the following steps:

[0006] S1. Preparation of modified acid-resistant fibers

[0007] Polyimide chips and polytetrafluoroethylene emulsion are fed into a twin-screw extruder, wherein the mass ratio of polyimide chips to polytetrafluoroethylene emulsion is 4-5:1; they are melt-blended at a temperature of 275-295℃, and then spun through a spinneret to obtain nascent fibers; the nascent fibers are subjected to hot stretching treatment to obtain modified acid-resistant fibers.

[0008] S2, Fiber-blended web

[0009] Take 15-25 wt% of polyphenylene sulfide fiber, 15-25 wt% of PE / PP core-sheath bicomponent fiber, and the balance of the modified acid-resistant fiber, and feed them into an opening machine for mixing and carding to a basis weight of 70-90 g / m². 2 A uniform fiber web;

[0010] S3, Gradient Hydroentanglement Reinforcement

[0011] The fiber web is sequentially passed through a pre-reinforcement zone, a flat web reinforcement zone, and a drum reinforcement zone of a hydroentangling device for hydroentangling reinforcement to obtain a hydroentangled nonwoven fabric. The pre-reinforcement zone has a single hydroentanglement head with a pressure of 45-55 bar. The flat web reinforcement zone has two hydroentanglement heads with pressures of 60-65 bar and 70-75 bar, respectively. The drum reinforcement zone has three hydroentanglement heads with pressures of 70-75 bar, 60-65 bar, and 55-60 bar, respectively.

[0012] S4, Interface Enhancement Processing

[0013] Take an epoxy-modified polyurethane emulsion with a mass concentration of 7-9% and a pH of 6.5, immerse the spunlace nonwoven fabric in the epoxy-modified polyurethane emulsion, with a roll-off rate of 37-43%, and obtain cross-linked network fibers after curing in a hot air circulating oven.

[0014] S5, Surface Functional Coating

[0015] CaF2 nanoparticles and PVP were ultrasonically dispersed in ethanol to obtain a CaF2 predispersant, wherein the CaF2 nanoparticles accounted for 18-22 wt%, PVP accounted for 3-5 wt%, and the balance was ethanol; the CaF2 predispersant was mixed with PVDF emulsion and deionized water, and stirred at 800-1000 rpm for 20-30 min to obtain a composite aqueous emulsion, wherein the CaF2 predispersant accounted for 25 wt%, PVDF emulsion accounted for 30 wt%, and the balance was deionized water;

[0016] The cross-linked network fibers are immersed in the composite aqueous emulsion for 15-25 seconds, and then extruded through rollers with a roll rate of 37-43%, forming a composite aqueous emulsion layer on the surface of the cross-linked network fibers. When the moisture content of the composite aqueous emulsion layer drops to 12-18%, a fiber laser is used to etch the surface, forming a micro-pit array with a diameter of 8-12 μm and a depth of 3-7 μm. Subsequently, it is hot-pressed and shaped by calendering rollers at 135-145℃ to obtain a water-repellent and acid-resistant nonwoven fabric.

[0017] Note: The hot pressing and shaping of the calender roller can simultaneously achieve coating consolidation and fiber morphology stabilization; the micro-dimples can improve the particle retention efficiency through capillary effect; the PE / PP core-sheath fiber can also reduce the overall density, meeting the lightweight requirements of filter cloth.

[0018] Furthermore, the spinneret in S1 has an orifice diameter of 0.1-0.2 mm and a spinning speed of 700-900 m / min.

[0019] Note: A 0.1-0.2mm small-aperture spinneret combined with a spinning speed of 700-900m / min is used to balance melt flow stability and fiber fineness control. The small-aperture design reduces melt orifice expansion and lowers the fiber breakage rate; medium-speed spinning ensures that the nascent fibers form a highly oriented, low-crystallinity structure, providing a uniform pre-oriented substrate for subsequent hot stretching and avoiding molecular chain deentanglement and strength loss caused by high speed.

[0020] Further, the hot stretching treatment method described in S1 is as follows: the nascent fiber is hot stretched by three sets of hot rollers, the temperatures of the three sets of hot rollers being 118-122℃, 128-135℃, and 138-145℃ respectively, to obtain modified acid-resistant fiber with a single diameter of 10-20μm.

[0021] Explanation: The low temperature range of 118-122℃ can soften the fiber surface, initiate molecular slip in the amorphous region, and reduce internal stress cracks; the medium temperature range of 128-135℃ can stimulate crystal nucleus growth and improve crystallinity; the high temperature range of 138-145℃ can complete crystal region recombination, enabling precise control of the single filament diameter, improving fracture strength and enhancing acid corrosion resistance.

[0022] Furthermore, the mass ratio of the PE sheath to the PP core layer of the PE / PP sheath-core bicomponent fiber described in S2 is 1:1-4.

[0023] Explanation: The PP core layer provides a rigid skeleton to maintain the dimensional stability of the fiber web at high temperatures; the PE sheath enhances the thermal bonding between fibers, reduces the fuzzing rate during hydroentangling reinforcement, and at the same time gives the fiber web flexibility and resilience.

[0024] Furthermore, the curing temperature of the hot air circulating oven described in S4 is 130-150℃, and the curing time is 4-6 minutes.

[0025] Note: Curing at 130-150℃ for 4-6 minutes can promote efficient cross-linking between epoxy groups and polyurethane prepolymer; ensure cross-linking density is greater than 85% to form a continuous protective film; control the curing time to avoid fiber yellowing, while improving interfacial peel strength and significantly blocking capillary penetration of acid.

[0026] Further, the PVDF emulsion in S5 is composed of 40-50 wt% PVDF resin particles, 0.1-1 wt% surfactant, 0.1-0.5 wt% dispersant, 2-3 wt% emulsifier, 0.1-0.3 wt% pH adjuster, and the balance being deionized water; the ultrasonic dispersion power is 150-250 W, the processing time is 10-15 min, and the controlled temperature is 25-30 °C.

[0027] Note: When compounded with the pre-dispersion liquid, the total solids content is close to 35%, ensuring the leveling properties of the coating; ultrasonic temperature control can inhibit CaF2 agglomeration caused by ethanol volatilization.

[0028] Furthermore, the fiber laser in S5 has a power of 19-21W and a scanning speed of 90-110mm / s; the linear pressure of the calendering roller is 60kgf / cm.

[0029] Note: Low power and high scanning can avoid carbonization microcracks and increase the specific surface area by 30%; 60 kgf / cm linear pressure can compact the burrs at the edge of the pit, maintain the porosity of more than 95%, and achieve aerosol retention and hydrophobic durability.

[0030] Furthermore, the steps also include post-processing, the post-processing method being: baking the water-repellent and acid-resistant nonwoven fabric in an oven at 175-185℃ for 25-35 seconds, and then smoothing the surface with a soft calendering roller at 165-175℃; the pressure of the soft calendering roller is 45-55 kgf / cm.

[0031] Note: Baking at 175-185℃ eliminates internal stress in the coating, and combined with a soft pressing roller, it improves flatness, avoids micro-pits and collapse caused by high pressure, and maintains air permeability.

[0032] The beneficial effects of this invention are:

[0033] This invention achieves enhanced structural stability, corrosion resistance, and surface functionalization of nonwoven fabrics used for filtering acid-washed waste gas through multi-stage composite modification. Polyphenylene sulfide fibers provide a heat-resistant skeleton, PE / PP core fibers enhance flexibility and resilience, and polyimide / PTFE blended modified fibers provide a core acid-resistant barrier. This is combined with a pre-reinforced zone with single-water-spinning heads for initial shaping under medium pressure, a flat web zone with double-water-spinning heads for high-pressure progressive entanglement, and a drum zone with triple-water-spinning heads for pressure reduction and surface refinement, forming a high-strength, breathable three-dimensional fiber network substrate. The epoxy-modified polyurethane crosslinking interface further enhances the fiber's performance. Enhanced with a pick-up rate of 37-43% for precise penetration, a continuous polymer protective layer is constructed to effectively block the penetration of acidic media. Further, a double-sided coating with CaF2-PVDF composite emulsion is applied, using CaF2 nanoparticles to improve surface hardness and slow-release fluoride ions for corrosion protection, and PVDF to enhance hydrophobicity. Coupled with laser etching of micro-pit arrays to form a rough surface structure, the superhydrophobicity and microparticle retention are enhanced, enabling the nonwoven fabric to maintain high-efficiency filtration accuracy in strong acid, high temperature and high humidity environments, while improving mechanical strength and extending service life. Detailed Implementation

[0034] To further illustrate the methods and effects of this invention, the technical solution of this invention will be clearly and completely described below in conjunction with experiments.

[0035] Example 1:

[0036] A method for preparing a water-repellent and acid-resistant nonwoven fabric for filtering exhaust gas from an acid pickling production line includes the following steps:

[0037] S1. Preparation of modified acid-resistant fibers

[0038] Polyimide chips and polytetrafluoroethylene emulsion are fed into a twin-screw extruder, with a mass ratio of 4.5:1. The mixture is melt-blended at 285°C and then spun through a spinneret to obtain nascent fibers. The nascent fibers are then subjected to a hot stretching treatment to obtain modified acid-resistant fibers.

[0039] The spinneret has an orifice diameter of 0.15 mm and a spinning speed of 800 m / min;

[0040] The hot stretching treatment method is as follows: the nascent fiber is hot stretched through three sets of hot rollers, the temperatures of the three sets of hot rollers are 120℃, 130℃ and 140℃ respectively, to obtain modified acid-resistant fiber with a single diameter of 15-16μm.

[0041] S2, Fiber-blended web

[0042] Take 20 wt% of polyphenylene sulfide fiber, 20 wt% of PE / PP core-sheath bicomponent fiber, and the balance of the modified acid-resistant fiber, and feed them into an opening machine for mixing and carding to a basis weight of 80 g / m². 2A uniform fiber web;

[0043] The mass ratio of the PE sheath to the PP core layer in the PE / PP bicomponent fiber is 1:2.5.

[0044] S3, Gradient Hydroentanglement Reinforcement

[0045] The fiber web is sequentially passed through the pre-reinforcement zone, flat web reinforcement zone, and drum reinforcement zone of a hydroentangling device for hydroentangling reinforcement to obtain a hydroentangled nonwoven fabric. The hydroentangling device is a commercially available hydroentangling machine. The pre-reinforcement zone has a single hydroentangling head with a pressure of 50 bar. The flat web reinforcement zone has two hydroentangling heads with pressures of 62.5 bar and 72.5 bar, respectively. The drum reinforcement zone has three hydroentangling heads with pressures of 72.5 bar, 62.5 bar, and 57.5 bar, respectively.

[0046] S4, Interface Enhancement Processing

[0047] An epoxy-modified polyurethane emulsion with a mass concentration of 8% and a pH of 6.5 was used to impregnate the spunlace nonwoven fabric with a roll-off rate of 40%. After curing in a hot air circulating oven, cross-linked network fibers were obtained.

[0048] The curing temperature of the hot air circulating oven is 140℃, and the curing time is 5 minutes.

[0049] S5, Surface Functional Coating

[0050] CaF2 nanoparticles and PVP were ultrasonically dispersed in ethanol to obtain a CaF2 predispersant, wherein the CaF2 nanoparticles accounted for 20 wt%, PVP accounted for 4 wt%, and the balance was ethanol; the CaF2 predispersant was mixed with PVDF emulsion and deionized water and stirred at 900 rpm for 25 min to obtain a composite aqueous emulsion, wherein the CaF2 predispersant accounted for 25 wt%, PVDF emulsion accounted for 30 wt%, and the balance was deionized water;

[0051] The PVDF emulsion consists of 46 wt% PVDF resin particles, 0.5 wt% surfactant, 0.3 wt% dispersant, 2.5 wt% emulsifier, 0.2 wt% pH adjuster, and the balance deionized water; the ultrasonic dispersion power is 200W, the processing time is 12.5 min, and the controlled temperature is 27.5℃.

[0052] The cross-linked network fibers are immersed in the composite aqueous emulsion for 20 seconds, and then extruded through rollers with a roll rate of 40%, forming a composite aqueous emulsion layer on the surface of the cross-linked network fibers. When the moisture content of the composite aqueous emulsion layer drops to 15%, a fiber laser is used to etch the surface, forming a micro-pit array with a diameter of 9-10 μm and a depth of 5-6 μm. Subsequently, it is hot-pressed and shaped by calendering rollers at 140°C to obtain a water-repellent and acid-resistant nonwoven fabric.

[0053] The fiber laser has a power of 20W and a scanning speed of 100mm / s; the linear pressure of the calendering roller is 60kgf / cm.

[0054] Example 2: This example is basically the same as Example 1, except that the steps also include post-processing. The post-processing method is as follows: the water-repellent and acid-resistant nonwoven fabric is baked in an oven at 175°C for 25 seconds, and then the surface is smoothed by a soft pressing roller at 165°C; the pressure of the soft pressing roller is 45 kgf / cm.

[0055] Example 3: This example is basically the same as Example 1, except that the steps also include post-processing. The post-processing method is as follows: the water-repellent and acid-resistant nonwoven fabric is baked in an oven at 180°C for 30 seconds, and then the surface is smoothed by a soft calendering roller at 170°C; the pressure of the soft calendering roller is 50 kgf / cm.

[0056] Example 4: This example is basically the same as Example 1, except that the steps also include post-processing. The post-processing method is as follows: the water-repellent and acid-resistant nonwoven fabric is baked in an oven at 185°C for 35 seconds, and then the surface is smoothed by a soft pressing roller at 175°C; the pressure of the soft pressing roller is 55 kgf / cm.

[0057] Example 5: This example is basically the same as Example 1, except that the mass ratio of the polyimide chips to the polytetrafluoroethylene emulsion is 4:1; the mixture is melt-blended at 275°C; 15 wt% of polyphenylene sulfide fiber, 15 wt% of PE / PP core-sheath bicomponent fiber, and the remainder of the modified acid-resistant fiber are fed into an opening machine for mixing and carding to a basis weight of 70 g / m². 2 A uniform fiber web.

[0058] Example 6: This example is basically the same as Example 1, except that the mass ratio of the polyimide chips to the polytetrafluoroethylene emulsion is 5:1; the mixture is melt-blended at 295°C; 25 wt% of polyphenylene sulfide fiber, 25 wt% of PE / PP core-sheath bicomponent fiber, and the remainder of the modified acid-resistant fiber are fed into an opening machine for mixing and carding to a basis weight of 90 g / m². 2 A uniform fiber web.

[0059] Example 7: This example is basically the same as Example 1, except that the pressure of the single water jet head is 45 bar; the flat mesh reinforcement area is a double water jet head with pressures of 60 bar and 70 bar respectively; and the drum reinforcement area is a triple water jet head with pressures of 70 bar, 60 bar and 55 bar respectively.

[0060] Example 8: This example is basically the same as Example 1, except that the pressure of the single water jet head is 55 bar; the flat mesh reinforcement area is a double water jet head with pressures of 65 bar and 75 bar respectively; and the drum reinforcement area is a triple water jet head with pressures of 75 bar, 65 bar and 60 bar respectively.

[0061] Example 9: This example is basically the same as Example 1, except that an epoxy-modified polyurethane emulsion with a mass concentration of 7% and a pH of 6.5 is used to impregnate the spunlace nonwoven fabric in the epoxy-modified polyurethane emulsion with a roll-off rate of 37%. After curing in a hot air circulating oven, cross-linked network fibers are obtained.

[0062] Example 10: This example is basically the same as Example 1, except that an epoxy-modified polyurethane emulsion with a mass concentration of 9% and a pH of 6.5 is used to impregnate the spunlace nonwoven fabric in the epoxy-modified polyurethane emulsion with a roll-off rate of 43%. After curing in a hot air circulating oven, cross-linked network fibers are obtained.

[0063] Example 11: This example is basically the same as Example 1, except that CaF2 nanoparticles and PVP are ultrasonically dispersed in ethanol to obtain a CaF2 pre-dispersion. In the CaF2 pre-dispersion, CaF2 nanoparticles account for 18 wt%, PVP accounts for 3 wt%, and the remainder is ethanol. The CaF2 pre-dispersion is mixed with PVDF emulsion and deionized water and stirred at 800 rpm for 20 min to obtain a composite aqueous emulsion. In the composite aqueous emulsion, CaF2 pre-dispersion accounts for 25 wt%, PVDF emulsion accounts for 30 wt%, and the remainder is deionized water.

[0064] The cross-linked network fibers are immersed in the composite aqueous emulsion for 15 seconds, and then extruded through rollers with a roll rate of 37%, forming a composite aqueous emulsion layer on the surface of the cross-linked network fibers. When the moisture content of the composite aqueous emulsion layer drops to 12%, a fiber laser is used to etch the surface to form a micro-pit array with a diameter of 8-9 μm and a depth of 3-4 μm. Subsequently, it is hot-pressed and shaped by calendering rollers at 135℃ to obtain a water-repellent and acid-resistant nonwoven fabric.

[0065] Example 12: This example is basically the same as Example 1, except that CaF2 nanoparticles and PVP are ultrasonically dispersed in ethanol to obtain a CaF2 pre-dispersion. In the CaF2 pre-dispersion, CaF2 nanoparticles account for 22 wt%, PVP accounts for 5 wt%, and the remainder is ethanol. The CaF2 pre-dispersion is mixed with PVDF emulsion and deionized water and stirred at 1000 rpm for 30 min to obtain a composite aqueous emulsion. In the composite aqueous emulsion, CaF2 pre-dispersion accounts for 25 wt%, PVDF emulsion accounts for 30 wt%, and the remainder is deionized water.

[0066] The cross-linked network fibers are immersed in the composite aqueous emulsion for 25 seconds, and then extruded through rollers with a roll rate of 43%, forming a composite aqueous emulsion layer on the surface of the cross-linked network fibers. When the moisture content of the composite aqueous emulsion layer drops to 18%, a fiber laser is used to etch the surface to form a micro-pit array with a diameter of 11-12 μm and a depth of 6-7 μm. Subsequently, it is hot-pressed and shaped by calendering rollers at 145℃ to obtain a water-repellent and acid-resistant nonwoven fabric.

[0067] Example 13: This example is basically the same as Example 1, except that the spinneret in S1 has an aperture of 0.1 mm and a spinning speed of 700 m / min; the hot stretching treatment method is as follows: the nascent fiber is hot stretched by three sets of hot rollers, the temperatures of the three sets of hot rollers are 118℃, 128℃ and 138℃ respectively, to obtain modified acid-resistant fiber with a single diameter of 10-11 μm; the mass ratio of PE sheath to PP core of the PE / PP sheath-core bicomponent fiber in S2 is 1:1; the curing temperature of the hot air circulating oven in S4 is 130℃ and the curing time is 4 min.

[0068] Example 14: This example is basically the same as Example 1, except that the spinneret in S1 has an aperture of 0.2 mm and a spinning speed of 900 m / min; the hot stretching treatment method is as follows: the nascent fiber is hot stretched by three sets of hot rollers, the temperatures of the three sets of hot rollers are 122℃, 135℃ and 145℃ respectively, to obtain a modified acid-resistant fiber with a single diameter of 20 μm; the mass ratio of the PE sheath and PP core of the PE / PP sheath-core bicomponent fiber in S2 is 1:4; the curing temperature of the hot air circulating oven in S4 is 150℃ and the curing time is 6 min.

[0069] Example 15: This example is basically the same as Example 1, except that the PVDF emulsion in S5 is composed of 40wt% PVDF resin particles, 0.1wt% surfactant, 0.1wt% dispersant, 2wt% emulsifier, 0.1wt% pH adjuster, and the balance deionized water; the ultrasonic dispersion power is 150W, the processing time is 10min, and the controlled temperature is 25℃.

[0070] Example 16: This example is basically the same as Example 1, except that the PVDF emulsion in S5 is composed of 50wt% PVDF resin particles, 1wt% surfactant, 0.5wt% dispersant, 3wt% emulsifier, 0.3wt% pH adjuster and the balance deionized water; the ultrasonic dispersion power is 250W, the processing time is 15min, and the controlled temperature is 30℃.

[0071] Example 17: This example is basically the same as Example 1, except that the power of the fiber laser in S5 is 19W and the scanning speed is 90mm / s; the linear pressure of the calendering roller is 60kgf / cm.

[0072] Example 18: This example is basically the same as Example 1, except that the power of the fiber laser in S5 is 21W and the scanning speed is 110mm / s; the linear pressure of the calendering roller is 60kgf / cm.

[0073] Comparative Example 1: Referring to Example 1, the difference is that the mass ratio of the polyimide chips to the polytetrafluoroethylene emulsion is 3:1; the mixture is melt-blended at 220°C; 10 wt% of polyphenylene sulfide fiber, 10 wt% of PE / PP core-sheath bicomponent fiber, and the remainder of the modified acid-resistant fiber are fed into an opening machine for mixing and carding to a basis weight of 60 g / m². 2 A uniform fiber web.

[0074] Comparative Example 2: Referring to Example 1, the difference is that the mass ratio of the polyimide chips to the polytetrafluoroethylene emulsion is 6:1; the mixture is melt-blended at 320°C; 30 wt% of polyphenylene sulfide fiber, 30 wt% of PE / PP core-sheath bicomponent fiber, and the remainder of the modified acid-resistant fiber are fed into an opening machine for mixing and carding to a basis weight of 100 g / m². 2 A uniform fiber web.

[0075] Comparative Example 3: Referring to Example 1, commercially available non-woven fabric for waste gas filtration produced by the SanTi Clean brand was used.

[0076] To investigate the nonwoven fabric properties of the above embodiments and control examples, the main materials were determined according to the experimental formulation, and samples were obtained for testing. The results are shown in Table 1. The specific investigation is as follows:

[0077] Table 1 Performance test results of hollow fiber ultrafiltration membrane samples from Examples 1-18 and Comparative Examples 1-3

[0078]

[0079]

[0080] 1. Investigate the impact of post-processing techniques on the properties of nonwoven fabric samples:

[0081] As shown in Table 1, a comparison of Examples 1-4 reveals that Example 1 achieved a filtration efficiency of 99.98% and had the optimal contact angle of 158°. Example 3, due to its post-treatment temperature of 170°C and soft pressing, achieved sufficient β-crystal transformation, resulting in a fracture strength of 2850N. Examples 2 and 4 experienced a slight decrease in performance due to deviations in post-treatment parameters, but were still significantly better than the other groups. This demonstrates that post-treatment temperature control is a key factor in improving strength.

[0082] 2. Investigate the effects of fiber ratio and process adjustment on the properties of nonwoven fabric samples:

[0083] As shown in Table 1, a comparison of Examples 5-10 reveals that Example 5, with a PI / PTFE ratio of 4:1 and a basis weight of 70 g / m³, is significantly superior. 2 The contact angle decreased to 152°; Example 6 was achieved due to the high basis weight of the comb, i.e., 90 g / m². 2 This maintains the filtration efficiency at 99.95%, but reduces flexibility;

[0084] In Example 9, the 7% epoxy emulsion concentration led to weakened interfacial bonding and a 4.3% loss in tensile strength. This demonstrates that the fiber ratio and interfacial treatment concentration must be strictly matched. The control range of fiber ratio and interfacial treatment concentration in this scheme has a significant impact on the performance optimization of the prepared filter nonwoven fabric.

[0085] 3. Investigate the effect of process parameter adjustment on the performance of nonwoven fabric samples:

[0086] As shown in Table 1, a comparison of Examples 11-18 reveals the following: In Example 13, the contact angle was only 148°, likely due to the small fiber diameter (10 μm) and low-temperature curing. In Example 16, the contact angle reached 155% possibly due to the sufficient dispersion of CaF2 by the ultrasonic power of 250W. This demonstrates that the laser etching depth significantly affects the filtration efficiency. The filtration efficiency of Example 12 was 99.96%, while that of Example 11 was only 99.91%. This proves that changes in the high-energy dispersion and etching depth process parameters can have a significant impact on the enhancement of the functional coating.

[0087] In Comparative Example 1, due to the imbalance of the PI / PTFE ratio (3:1) and low-temperature melting, the interfacial compatibility was poor, and its acid contact angle dropped sharply to 132°; in Comparative Example 2, due to the high basis weight of the comb (100 g / m²), the acid contact angle dropped sharply to 132°. 2 This leads to pore blockage, resulting in an efficiency of only 99.35%. It is speculated that the performance of the commercially available product in Comparative Example 3 is far inferior to that of the example group that prepared nonwoven fabric using this method due to the lack of composite coating and laser etching treatment. The nonwoven fabric prepared using the parameters within the parameter range of this method has better overall performance.

Claims

1. A method for preparing a water-repellent and acid-resistant nonwoven fabric for filtering exhaust gas from an acid pickling production line, characterized in that, Includes the following steps: S1. Preparation of modified acid-resistant fibers Polyimide chips and polytetrafluoroethylene emulsion are fed into a twin-screw extruder, wherein the mass ratio of polyimide chips to polytetrafluoroethylene emulsion is 4-5:1; they are melt-blended at a temperature of 275-295℃, and then spun through a spinneret to obtain nascent fibers; the nascent fibers are subjected to hot stretching treatment to obtain modified acid-resistant fibers. S2, Fiber-blended web Take 15-25 wt% of polyphenylene sulfide fiber, 15-25 wt% of PE / PP core-sheath bicomponent fiber, and the balance of the modified acid-resistant fiber, and feed them into an opening machine for mixing and carding to a basis weight of 70-90 g / m². 2 A uniform fiber web; S3, Gradient Hydroentanglement Reinforcement The fiber web is sequentially passed through a pre-reinforcement zone, a flat web reinforcement zone, and a drum reinforcement zone of a hydroentangling device for hydroentangling reinforcement to obtain a hydroentangled nonwoven fabric. The pre-reinforcement zone has a single hydroentanglement head with a pressure of 45-55 bar. The flat web reinforcement zone has two hydroentanglement heads with pressures of 60-65 bar and 70-75 bar, respectively. The drum reinforcement zone has three hydroentanglement heads with pressures of 70-75 bar, 60-65 bar, and 55-60 bar, respectively. S4, Interface Enhancement Processing Take an epoxy-modified polyurethane emulsion with a mass concentration of 7-9% and a pH of 6.5, immerse the spunlace nonwoven fabric in the epoxy-modified polyurethane emulsion, with a roll-off rate of 37-43%, and obtain cross-linked network fibers after curing in a hot air circulating oven. S5, Surface Functional Coating CaF2 nanoparticles and PVP were ultrasonically dispersed in ethanol to obtain a CaF2 predispersant, wherein the CaF2 nanoparticles accounted for 18-22 wt%, PVP accounted for 3-5 wt%, and the balance was ethanol; the CaF2 predispersant was mixed with PVDF emulsion and deionized water, and stirred at 800-1000 rpm for 20-30 min to obtain a composite aqueous emulsion, wherein the CaF2 predispersant accounted for 25 wt%, PVDF emulsion accounted for 30 wt%, and the balance was deionized water; The cross-linked network fibers are immersed in the composite aqueous emulsion for 15-25 seconds, and then extruded through rollers with a roll rate of 37-43%, forming a composite aqueous emulsion layer on the surface of the cross-linked network fibers. When the moisture content of the composite aqueous emulsion layer drops to 12-18%, a fiber laser is used to etch the surface, forming a micro-pit array with a diameter of 8-12 μm and a depth of 3-7 μm. Subsequently, it is hot-pressed and shaped by calendering rollers at 135-145℃ to obtain a water-repellent and acid-resistant nonwoven fabric.

2. The method for preparing a water-repellent and acid-resistant nonwoven fabric for filtering exhaust gas from an acid pickling production line according to claim 1, characterized in that, The spinneret described in S1 has an orifice diameter of 0.1-0.2 mm and a spinning speed of 700-900 m / min.

3. The method for preparing a water-repellent and acid-resistant nonwoven fabric for filtering exhaust gas from an acid pickling production line according to claim 1, characterized in that, The hot stretching treatment method described in S1 is as follows: the nascent fiber is hot stretched by three sets of hot rollers, the temperatures of the three sets of hot rollers being 118-122℃, 128-135℃, and 138-145℃ respectively, to obtain modified acid-resistant fiber with a single diameter of 10-20μm.

4. The method for preparing a water-repellent and acid-resistant nonwoven fabric for filtering exhaust gas from an acid pickling production line according to claim 1, characterized in that, The mass ratio of the PE sheath to the PP core of the PE / PP bicomponent fiber described in S2 is 1:1-4.

5. The method for preparing a water-repellent and acid-resistant nonwoven fabric for filtering exhaust gas from an acid pickling production line according to claim 1, characterized in that, The curing temperature of the hot air circulating oven described in S4 is 130-150℃, and the curing time is 4-6 minutes.

6. The method for preparing a water-repellent and acid-resistant nonwoven fabric for filtering exhaust gas from an acid pickling production line according to claim 1, characterized in that, The PVDF emulsion described in S5 consists of 40-50 wt% PVDF resin particles, 0.1-1 wt% surfactant, 0.1-0.5 wt% dispersant, 2-3 wt% emulsifier, 0.1-0.3 wt% pH adjuster, and the balance being deionized water; the ultrasonic dispersion power is 150-250 W, the processing time is 10-15 min, and the controlled temperature is 25-30℃.

7. The method for preparing a water-repellent and acid-resistant nonwoven fabric for filtering exhaust gas from an acid pickling production line according to claim 1, characterized in that, The fiber laser in S5 has a power of 19-21W and a scanning speed of 90-110mm / s; the linear pressure of the calendering roller is 60kgf / cm.

8. The method for preparing a water-repellent and acid-resistant nonwoven fabric for filtering exhaust gas from an acid pickling production line according to claim 1, characterized in that, The steps also include post-processing, which involves baking the water-repellent and acid-resistant nonwoven fabric in an oven at 175-185℃ for 25-35 seconds, and then smoothing the surface with a soft calendering roller at 165-175℃; the pressure of the soft calendering roller is 45-55 kgf / cm.